2010
DOI: 10.4137/cmt.s1103
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy Update: Pregabalin in the Treatment of Generalized Anxiety Disorder

Abstract: Generalized anxiety disorder (GAD) is a common disorder that is chronic, disabling, and often goes undiagnosed. Currently, four distinct classes of medications have demonstrated efficacy in the treatment of GAD: benzodiazepines, serotonin and/or norepinephrine reuptake inhibitors (SSRIs/SNRIs), histamine H 1 receptor blockers (hydroxyzine), and pregabalin. Pregabalin acts via binding to an α2-δ subunit presynaptic membrane protein that inhibits neurotransmitter release in excited neurons. Pregabalin is renally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
6
0
2
Order By: Relevance
“…In addition to safety data contained in the clinical trials cited above, four additional citations summarised results of studies with safety as the primary outcome (Frame et al, 2009; Hindmarch et al, 2005a, 2005b; Rubio et al, 2011). Finally, 11 review articles were identified that specifically evaluated the safety and efficacy of pregabalin in the treatment of GAD (Bandelow et al, 2007; Bech, 2007; Boschen, 2011, 2012; Frampton and Foster, 2006; Holsboer-Trachsler and Prieto, 2013; Lauria-Horner and Pohl, 2003; Montgomery, 2006; Montgomery and Kasper, 2010; Owen, 2007; Wensel et al, 2012). These articles were each reviewed to determine whether they contained additional citations not identified in the MEDLINE and PsychINFO literature searches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to safety data contained in the clinical trials cited above, four additional citations summarised results of studies with safety as the primary outcome (Frame et al, 2009; Hindmarch et al, 2005a, 2005b; Rubio et al, 2011). Finally, 11 review articles were identified that specifically evaluated the safety and efficacy of pregabalin in the treatment of GAD (Bandelow et al, 2007; Bech, 2007; Boschen, 2011, 2012; Frampton and Foster, 2006; Holsboer-Trachsler and Prieto, 2013; Lauria-Horner and Pohl, 2003; Montgomery, 2006; Montgomery and Kasper, 2010; Owen, 2007; Wensel et al, 2012). These articles were each reviewed to determine whether they contained additional citations not identified in the MEDLINE and PsychINFO literature searches.…”
Section: Methodsmentioning
confidence: 99%
“…It appears to achieve its anxiolytic effect by binding to the α 2 δ subunit of the P/Q-type of voltage-gated calcium channel, resulting in a reduction in neurotransmission in excited neurons (Micó and Prieto, 2012). At the time of writing this review, it has been three years since the last comprehensive review of the efficacy and safety of pregabalin in GAD was published (Montgomery and Kasper, 2010). Since then, a brief clinical review has appeared that examines published data up to December 2011 (Wensel et al, 2012), but the availability of several recently published clinical trials of pregabalin suggests a new review might be useful.…”
Section: Introductionmentioning
confidence: 99%
“…While these results present some suggestion that moderate doses of pregabalin may be associated with greatest reduction in anxiety symptoms, high doses (i. e., those above 450 mg/day) may not provide additional benefi ts, but still expose the patient to higher risk of adverse events. In previous research on pregabalin in the treatment of GAD, adverse events have been higher on a dose of 600 mg/day compared with lower doses [ 27 ] . Adverse events such as dizziness and somnolence may also make independent contributions to functional impairment if they are severe and/or prolonged.…”
Section: Discussion ▼mentioning
confidence: 94%
“…The treatment of patients with GAD in our study raised certain issues. The most interesting result is the high rate of prescriptions of pregabalin [19,20,26]; it was prescribed for 29.1 % of patients with GAD in the years 2009-2011. From 1997 to 2011, the prescription rate of anticonvulsants showed a significant annual increase, and as in 2004, pregabalin was approved for the treatment of GAD by the European Medicines Agency (EMA).…”
Section: Comparison To Guidelines For the Treatment Of Gadmentioning
confidence: 95%